Swearing and Taboo Words by The Main Character in I, Tonya Movie - Dewi, Komang Yuly Sintia; Indriani, Ketut Santi (Humanis; Vol 25 No 2 (2021), 2021)
The study was aimed to find out the types of swearing and taboo words and to analyze the emotion that influences the use of swearing and taboo words of the main character in I, Tonya movie. The data was collected by using the documentation method and note-taking technique from the movie I, Tonya. The movie was an American Biographical comedy-drama based on a true story of Tonya Harding’s life. The data was analyzed descriptive qualitatively with the reducing technique based on the theory of women’s language features proposed by Lakoff (2004) and the theory of Barrett (1985) about the constructed emotion as the supporting theory. The collection process has found 65 data in which five of them being reduced as it has similar explanations as the data being shown. Those five data with each of their emotional influences, namely bitches; arrogance, bullshit; disappointment, suck my dick; anger, fuck; pleasure and confident, god damn it; surprise and panic. Those five data showed the contradiction to the theory of Lakoff about women’s language particularly in using swear and taboo words.